Factors influencing the quality of life in inflammatory bowel disease: A comprehensive review - Khan, Samina; Sebastian, Sneha Annie; Parmar, Mihirkumar P.; Ghadge, Nitin; Padda, Inderbir; Keshta, Ahmed S.; Minhaz, Naofel; Patel, Apurva (Disease-a-month, 2024)
Inflammatory bowel disease (IBD) is a group of chronic relapsing disorders, including Crohn's disease (CD) and ulcerative colitis (UC), which affects an increasing number of people worldwide. In the last few decades, the scientific world has witnessed many developments in IBD management by controlling debilitating symptoms and remaining in remission for more protracted periods. Even so, we still have a large population suffering from active IBD. An individual's quality of life (QoL) can be severely affected by IBD, like any other chronic illness. In this article, we have reviewed factors influencing the QoL in IBD patients, including chronic pain, diet, physical activity, and psychological factors like depression, anxiety, and stress symptoms. We also discussed the mechanisms of diet-microbial-immune system interaction, currently available dietary therapies for active CD and UC, and early psycho-social interventions that can reduce the disease burden and improve QoL in IBD patients. [Display omitted]